Organic and inorganic nitrogen in precipitation and in forest throughfall at Bílý Kříž site (Beskydy Mts., Czech Republic) - I. Drápelová (Journal of Forest Science, 2012)
Organic nitrogen is an important but yet not very well explored component of nitrogen deposition. In this study concentrations and fluxes of organic and inorganic nitrogen in bulk precipitation in an open field (BOF) and in throughfall (THR) were evaluated at the Bílý Kříž experimental site (Moravian-Silesian Beskydy Mts., Czech Republic, 908 m a.s.l.) with a young Norway spruce stand. The results of a two-year study (2008 and 2009) were compared with the results obtained during the same time period on forest plots included in ICP Forests Programme in the Czech Republic. Total nitrogen deposition in BOF at the Bílý Kříž site amounted to about 918 mg.m-2.a-1, the contribution of organic nitrogen was about 8%. Total nitrogen flux with THR at Bílý Kříž was about 1,305 mg.m-2.a-1 during the studied years and organic N accounted for 12% of this amount. The ranges of the two-year average values found for total nitrogen flux on ICP Forests plots throughout the Czech Republic were as follows: 759-1,857 mg N.m-2.a-1 with 7-38% contribution of organic N in BOF and 928-3,816 mg N.m-2.a-1 with 7-20% contribution of organic N in THR. The share of organic nitrogen in THR nitrogen fluxes at Bílý Kříž proved clear seasonality with maxima in July. A highly significant correlation between N-NH4+ and N-NO3- concentrations in BOF suggested the common anthropogenic source of these substances at the Bílý Kříž site. No significant correlation was found either between organic N and N-NH4+ or between organic N and N-NO3- concentrations in BOF. Cumulative deposition charts showed different behaviour of particular nitrogen deposition components while passing through the canopy.